Regulation of voltage-gated potassium channels by PI(4,5)P2 - Kruse, Martin; Hammond, Gerald R V; Hille, Bertil (The Journal of general physiology, 2012)
Phosphatidylinositol 4,5-bisphosphate (PI(4,5)P(2)) regulates activities of numerous ion channels including inwardly rectifying potassium (K(ir)) channels, KCNQ, TRP, and voltage-gated calcium channels. Several studies suggest that voltage-gated potassium (K(V)) channels might be regulated by PI(4,5)P(2). Wide expression of K(V) channels in different cells suggests that such regulation could have broad physiological consequences. To study regulation of K(V) channels by PI(4,5)P(2), we have coexpressed several of them in tsA-201 cells with a G protein-coupled receptor (M(1)R), a voltage-sensitive lipid 5-phosphatase (Dr-VSP), or an engineered fusion protein carrying both lipid 4-phosphatase and 5-phosphatase activity (pseudojanin). These tools deplete PI(4,5)P(2) with application of muscarinic agonists, depolarization, or rapamycin, respectively. PI(4,5)P(2) at the plasma membrane was monitored by Förster resonance energy transfer (FRET) from PH probes of PLCδ1 simultaneously with whole-cell recordings. Activation of Dr-VSP or recruitment of pseudojanin inhibited K(V)7.1, K(V)7.2/7.3, and K(ir)2.1 channel current by 90-95%. Activation of M(1)R inhibited K(V)7.2/7.3 current similarly. With these tools, we tested for potential PI(4,5)P(2) regulation of activity of K(V)1.1/K(V)β1.1, K(V)1.3, K(V)1.4, and K(V)1.5/K(V)β1.3, K(V)2.1, K(V)3.4, K(V)4.2, K(V)4.3 (with different KChIPs and DPP6-s), and hERG/KCNE2. Interestingly, we found a substantial removal of inactivation for K(V)1.1/K(V)β1.1 and K(V)3.4, resulting in up-regulation of current density upon activation of M(1)R but no changes in activity upon activating only VSP or pseudojanin. The other channels tested except possibly hERG showed no alteration in activity in any of the assays we used. In conclusion, a depletion of PI(4,5)P(2) at the plasma membrane by enzymes does not seem to influence activity of most tested K(V) channels, whereas it does strongly inhibit members of the K(V)7 and K(ir) families.